Online marketing communication of non-profit organizations with focus on cancer awareness - Sklenářová, Jana (2017)
The main goal of this thesis is to analyze online marketing communication of non-profit organizations focused on cancer in the Czech Republic. Based on the results, provide recommendations how NGOs can leverage online marketing channels within their communication strategy. The thesis gives an overview of online activities of Czech non-profits focused on cancer. The theoretical part of the thesis concentrates on the classification of NGOs, different concepts of marketing in the non-profit segment and its development, specifics of online marketing strategy for non-profits, role and various types of digital media that NGOs can leverage within their marketing communication. The practical part provides analysis of online marketing communication of selected NGOs focused on cancer. Data were collected from personal interviews with selected non-profit organizations and desk research with the help of various analytical tools.